THE EFFECT OF SOCIAL MEDIA ON BRAND LOYALTY (STUDY CASE: FACEBOOK FAN PAGE FOR GROWING UP MILK IN INDONESIA) - Indah Tri Novita (Jurnal Manajemen Industri dan Logistik, 2021)
The issue for marketers resulting from the dramatic rise of social media usage is how fan pages can be leveraged to engage customers and create brand loyalty. This thesis discusses the effect of fan pages on brand loyalty and what motivates users to participate. This research is quantitative descriptive design. Data was gathered via a survey of 192 respondents of growing up milk fan pages and analyzed using Structural Equation Modelling. This study shows that there is a significant relationship between usage behavior on the fan page on brand loyalty. This research also identified that brand interaction as a driver for increasing the intensity of use of the fan page and self-concept value to increase the involvement. The results of this research suggest that the brand manager of social media sites should focus on increasing the traffic and create involvement, integrate, and make the fans active in the community.